NUMERICAL INVESTIGATION OF FAULT GOUGE MATERIAL (FGM) MECHANICAL BEHAVIOR UNDER THE INFLUENCE OF PORE PRESSURE AND LOADING CONDITIONS - Yaqoob, Muhammad (Nazarbayev University School Of Mining and Geosciences, 2024)
This research study presents a numerical analysis of the mechanical behavior of fault gouge materials (FGMs) using the finite element method (FEM) within the Abaqus computational analysis environment (CAE). The mechanical properties of fault zones are greatly influenced by fault gouge materials, which are fine-grained materials located inside fault planes. The mechanical behavior of FGM toward pore fluid pressure plays a crucial role in Carbon Capture and Storage (CCS) projects, which include the sequestration of CO2 inside geological formations. Previous research has shown the important role of fluid pore pressures in commencing fault displacement, which may either reduce or increase fault stability. Pore pressure fluctuation plays an important role in maintaining fault stability in completely saturated FGMs. The purpose of this thesis is to analyze the behavior of fluid-saturated fine-grained materials (FGMs) under both normal and shear loading situations using Abaqus Finite Element Method (FEM) analysis. The study intends to address the limitations of currently available prediction models and contribute to the advancement of geomechanics knowledge in the context of FGM. The comparative analysis evaluates the influence of pore pressure on the Fault Gouge Material (FGM) in both models. The FGM simulation findings indicate that the models without pore pressure exhibit slightly greater deformation compared to the models with pore pressure. However, while considering the elastic analysis, it is shown that the FGM demonstrates a greater degree of deformation when subjected to pore pressure under normal loading conditions.
Keywords: Type of access: Embargo; Fault Gouge materials (FGM); Geomechanics; Pore pressure; Abaqus Numerical modelling